2010
DOI: 10.1159/000277415
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acrodermatitis Continua of Hallopeau with TNF-Blocking Agents: Case Report and Review

Abstract: Acrodermatitis continua of Hallopeau (ACH) is a rare acropustular eruption, characterized by sterile pustules, paronychia and atrophic skin changes, onychodystrophy and osteolysis of the distal phalanges of the fingers and toes. It is considered to be a variant of pustular psoriasis with a chronic relapsing course and frequent refractoriness to many therapeutic modalities, which can be amenable to successful treatment by tumor necrosis factor α antagonists. We report 1 patient with pustular psoriasis and ACH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 59 publications
2
29
1
1
Order By: Relevance
“…Though anti-tumour necrosis factor (TNF) can induce palmoplantar pustular psoriasis (PPPP), it has been proven efficient for ACH. The results of 33 treatments with anti-TNF in 23 ACH patients have been reported so far [2,3,4,5,6,7]. In responsive patients, clearance of lesions was reported to occur more rapidly than in psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Though anti-tumour necrosis factor (TNF) can induce palmoplantar pustular psoriasis (PPPP), it has been proven efficient for ACH. The results of 33 treatments with anti-TNF in 23 ACH patients have been reported so far [2,3,4,5,6,7]. In responsive patients, clearance of lesions was reported to occur more rapidly than in psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from GPP, patients with PPPP are not at risk of developing life‐threatening complications, which remain a hallmark of GPP and of AGEP. However, palmar and/or plantar pustular involvement may associate with acropustular (ACH) presentation . Furthermore, some recent observations indicate that in patients with deficiency of interleukin‐36 receptor antagonist (DITRA), a localized initial phase of the disease may be followed by GPP attacks, emphasizing the complexity of genotype–phenotype correlation .…”
Section: Localized Pustular Psoriasismentioning
confidence: 99%
“…The acropustular pustular subtype of psoriasis is very rare, and is of a sporadic nature . However, it is interesting to notice that chronic ACH lesions have been reported to persist in between the systemic attacks in patients with GPP, including those with DITRA .…”
Section: Acrodermatitis Continua Of Hallopeaumentioning
confidence: 99%
“…Eventually, adalimumab 40 mg every 2 weeks has provided the most costeffective response in this patient, allowing maintenance of response with partial nail regrowth under monotherapy. Bonish et al also observed a case of etanercept responsive acrodermatitis continua of Hallopeau [12,13].…”
Section: -Acrodermatitis Continua Of Hallopeaumentioning
confidence: 99%